Stagnant zone formation on diamond cutting tools during machining - Sudin, Izman (2007)
Formation of an intact region on the rake face of cutting tool during machining is quite common phenomenon but its significance in maintaining tool edge sharpness has not been recognized by many researchers. This region is sometimes called stagnant zone. It is believed that when an intact zone present on the rake face, it delays the crater wear progress and hence maintaining the tool edge sharpness longer. This paper investigates the effect of edge radius, surface roughness of the rake face and cutting parameters on the formation of stagnant zone on two different type of diamond tools i.e. polycrystalline diamond PCD-KD100 and diamond-coated inserts when machining titanium alloy. The used inserta and post-processed chips were examined under FESEM and optical microscope after cutting at three different conditions. Experimental results show that the speed and feel, the tool edge radius, and the tool rake surface roughness significantly affect the stagnant zone formation.